Investigating the Role of Poxvirus Virulence Genes A35 and O1L in the Virus Life Cycle - Hayes, Alexandra G (East Carolina University, 2019)
Poxviruses, some of the largest viruses in existence, have a great impact on the human and animal world due to their ability to infect a broad assortment of organisms and cause significant disease. Today, poxvirus infections remain a danger to human health, as natural and potential bioterrorism threats. Vaccinia virus (VACV), the species of poxvirus used in smallpox vaccines, is the most studied poxvirus, but there is still much to learn in regards to its virulence factors and their role in the virus life cycle. Our laboratory has identified two VACV genes/proteins that play an important role in virulence, A35 and O1L, which we hypothesized were immunoregulatory, so their effects on host immune responses were assessed. We found that the A35 protein inhibits anti-viral antibody production and cytokine responses by T lymphocytes in vivo. However, there was no evidence to suggest that A35 inhibits recall antigen presentation by infected BMDC in vitro. There were also no A35 effects observed on VACV cell killing, replication, or integrin expression for bone marrow dendritic cells (BMDC), which were used as antigen presenting cells (APC). When looking at the function of O1L, we did not find an effect of O1L on anti-viral antibody production or T cell response, so the O1L effects on replication and spread, cell killing, integrin expression, cytokine production, and innate immunity were also measured. In each of these cases, the O1L deletion mutant (O1LDel) had a similar phenotype to the wild type virus. We did observe that plaques formed by the O1LDel virus appeared smaller in some cases compared to wild type plaques, which was due to reduced cell clearance in the center of the O1LDel plaques. However, the biological relevance of this finding is unclear at this time. The fact that the VACV O1L gene encodes a large protein that is conserved in mammalian tropic poxviruses with 92-100% homology supports that the gene performs an important function in the poxvirus life cycle. Our laboratory has shown that both A35 and O1L deletion viral mutants make safer vaccine alternatives against poxviruses. Understanding how poxviruses turn off immune responses will aid in our understanding of viral pathogenesis and support anti-viral drug design, improve vaccines, and may allow us to mimic poxvirus immunosuppression to control autoimmune diseases.
Keywords: poxvirus; vaccinia virus; A35; O1L; immunoregulatory; virulence; Virulence; Chordopoxvirinae; Poxviridae